2022
DOI: 10.3389/fnut.2022.895070
|View full text |Cite
|
Sign up to set email alerts
|

Oleuropein-Enriched Extract From Olive Mill Leaves by Homogenizer-Assisted Extraction and Its Antioxidant and Antiglycating Activities

Abstract: Olive oil consumption has increased in the last two decades and consequently, its wastes have increased, which generates a tremendous environmental impact. Among the by-products are the olive mill leaves, which are easier and inexpensive to treat than other olive by-products. However, little research has been done on their chemical composition and potential bioactivity. Hence, in this study, olive mill leaves were used to obtain Oleuropein-Enriched Extracts (OLEU-EE) using Conventional Extraction, Ultrasound-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 56 publications
2
7
0
Order By: Relevance
“…The remarkable reducing power of the OLEs indicates the effectiveness of the phenolic compounds and flavonoids, which might be beneficial in the treatment and/or prevention of several human diseases and which might have health promoting properties. This result emphasized previous work, which reported the high antioxidant activity and oxidative stability of olive leaf extracts [ 34 , 35 , 36 ]. Several in vitro and in vivo studies have reported phenolic compounds as showing anti-inflammatory, anti-microbial, anti-diabetic and anti-tumoral properties.…”
Section: Resultssupporting
confidence: 90%
“…The remarkable reducing power of the OLEs indicates the effectiveness of the phenolic compounds and flavonoids, which might be beneficial in the treatment and/or prevention of several human diseases and which might have health promoting properties. This result emphasized previous work, which reported the high antioxidant activity and oxidative stability of olive leaf extracts [ 34 , 35 , 36 ]. Several in vitro and in vivo studies have reported phenolic compounds as showing anti-inflammatory, anti-microbial, anti-diabetic and anti-tumoral properties.…”
Section: Resultssupporting
confidence: 90%
“…In a recent paper, examining olive mill leaves (Arbequina variety), Márquez et al , 31 found substantial effectiveness of the homogenizer-assisted extraction approach in the recovery of oleuropein (4345 mg/100 g). Moreover, Ahmad-Qasem et al , 32 compared different drying and freezing methods used before the extraction process and detected the highest recovery of oleuropein (108.6 mg per g extract, d.w.) when the leaves, prior to being extracted in a shaking water bath (22 °C for 24 h), were initially hot air dried at 120 °C for 12 min.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent paper, examining olive mill leaves (Arbequina variety), Márquez et al, 31 found substantial effectiveness of the homogenizer-assisted extraction approach in the recovery of oleuropein (4345 mg/100 g). Moreover, Ahmad-Qasem et al, 32 Fig.…”
Section: Recovery Of Principal Polar Phenols From Olive Leaveschromat...mentioning
confidence: 99%
“…It was similar also to that found in a recent work of del Mar Contreras et al [36] (22 mg GA/g of dry leaf), which was obtained after optimization of the extraction process. The high value of phenols (~52 mg GA/g of dry leaf) has been reported only by Marquez et al [37]. Such value could be ascribed to the technique adopted (homogenizerassisted extraction at 18,000 rpm) which, after optimization, provided better results than conventional and ultrasound-assisted extraction.…”
Section: Olive-leaf Examinationmentioning
confidence: 93%